Positive Politeness Strategies Used in “H3 Podcast#7” Youtube Video : Pragmatics Study - Insan Abi Pramaidana; Hero Gunawan (Universitas Cokroaminoto Palopo, 2022)
The purposes of this research are 1) to analyze and investigate the types of positive politeness used in “H3 Podcast #7 - Post Malone and Joji” YouTube video, and 2) to analyze the reason why positive politeness is used. The method used in this research is qualitative-descriptive method. The theoretical used in this research is the theory of positive politeness strategies from Brown and Levinson (1987). The results of this research indicate that there were two types of positive politeness strategies are found in the video: 1) claim common ground, and 2) convey that S (speaker) and H (hearer) are cooperators. There were three strategies used in the claim common ground: strategy-1: noticing, attending to hearer (32%), strategy-2: exaggerating interest, approval, sympathy with hearer (23%) and strategy-3: intensifying interest to hearer (16%). The strategies used related to the convey that S and H are cooperators cover three strategies, namely, strategy-1: assert or presuppose S’s knowledge of and concern for H’s wants (6%), strategy-2: offer, promise (13%) and strategy 3: be optimistic (10%). Therefore, the reason why positive politeness used in “H3 Podcast #7” is that the speakers concern with the hearer’s positive face, they tend to show the solidarity, emphasize that both speakers and hearers want the same thing, and they have a common goal. Politeness gets the speakers message delivered and responded to in the ways he/she wants.